A comprehensive 22-year global GNSS climate data record from 5085 stations - Xiaoming Wang; Haobo Li; Suelynn Choy; Qiuying Huang; Wenhui Cai; Anthony Rea; Hongxin Zhang; Luis Elneser; Yuriy Kuleshov (PANGAEA, 2025)
Abstract. This work presents a comprehensive global GNSS climate data record derived from 5085 stations, spanning a 22-year time period 2000–2021. Generated through the GPAC-Repro campaign, the dataset utilises state-of-the-art processing methodologies and precise products from the International GNSS Service (IGS) Repro-3 initiative. The dataset includes high-quality hourly estimates of Zenith Total Delay (ZTD) and Precipitable Water Vapour (PWV), offering improved accuracy and spatiotemporal coverage. A rigorous data screening and quality assessment framework was implemented, including formal error detection, offset identification, and extensive cross-validation with ERA5 reanalysis dataset, radiosonde profiles, and Very Long Baseline Interferometry (VLBI) measurements. Collectively, these efforts ensured the consistency, accuracy, and homogeneity of the dataset. The insights provided by the dataset address critical data gaps in global climate observing systems and provide a robust foundation for advancing climate research and applications.